Reviewing Mangrove Degradation, Conservation, and Restoration: A Sustainability Nexus Assessment on Myanmar Using the DPSIR Framework - Nyein, Lwin Thuzar; Karthe, Daniel; Giessen, Lukas; Babel, Mukand Singh; Schusser, Carsten (Forest and Society, 2025)
Mangrove forests are vital for supporting local livelihoods and are an integral component of coastal ecosystems in Myanmar. However, they continue to degrade or even disappear across the country’s coastal regions even though rehabilitation processes have been initiated in several regions. Still, little research and systematic inquiry into the drivers of mangrove degradation in Myanmar is available. Against this background, this study identifies the primary forces affecting the mangrove ecosystem and the challenges for mangrove conservation in Myanmar by combining a systematic literature review (SLR) on mangrove change with the Driver-Pressure-State-Impact-Response (DPSIR) analytical framework. We find economic activities, predominantly in agriculture, as the main drivers, resulting in pressure to convert mangroves to other land uses and leading to the degradation of mangrove forests and loss of mangrove ecosystem services. However, the regional patterns of crop production, firewood, and charcoal consumption have remained stable during the recent past. Further ground data measurements are still necessary to identify the primary factors causing mangrove degradation in Myanmar. The most commonly identified research methods were remote sensing methodologies while socio-political approaches were rarely considered in the context of mangrove preservation in Myanmar but are strongly needed in the future. This is underlined by the DPSIR analysis which identified adequate policy responses as a crucial element for mangrove protection and restoration. While a few measures on mangrove reforestation were documented in the literature, their long-term success has not been adequately assessed, including the implications that climate change will have on natural and restored mangrove systems. In the future, more studies on the social and actor-related aspects of mangrove ecosystem management are needed and have to consider the sustainability nexus of ecological goals and socio-economic development, considering all levels.